Macroeconomic implications of the underground sector : challenging the double business cycle approach (2011)
ABSTRACT: Within the literature on business cycles featuring shadow economic activities, there is an approach based on the arguable premise that fluctuations in the official and unofficial sectors are negatively correlated. The present paper develops a real business cycle model that does not impose such an assumption. To do so, preferences are characterized so that regular and irregular labor are additively separable. Furthermore, leisure time is spent on both irregular work effort and non-market activities. Simulations are conducted to examine the performance of the model economy and to compare the resulting cyclical features with related empirical findings. In addition, computational experiments allow to analyze the effects of different tax structures, enforcement rates and tastes for irregular labor on the volatility and comovements of aggregate variables. These simulations and experiments overall offer a more comprehensive view of the cyclical implications of the shadow economy.